Molly : an American girl on the home front [videorecording (DVD)] - Chopra, Joyce; Ritter, Maya. 1993-; Baker, David Aaron, 1963-; Green, Tory. 1994- (Warner Home Video, 2011)
World War II turns Molly's family upside down. While her father is away, war breaks out on the McIntires' home front.